1998
DOI: 10.3109/13814789809160362
|View full text |Cite
|
Sign up to set email alerts
|

How predictive is a home-safety checklist of indoor fall risk for the elderly living in the community?

Abstract: Development and evaluation of a homesafety checklist of indoor fall risk for the elderly living in the community. Methods: A checklist of indoor fall risk was developed in a Delphi procedure as part of a baseline assessment of fall risk. Based on the number of falls in the previous year, the 1238 responders to a postal questionnaire on occurrence, risk factors, and consequences of falls in community-living elderly of 70 years or over were divided into three groups: non fallers, one-time fallers and recurrent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…21,22 Environmental hazards were identified and registered using a home-safety checklist. 23 In addition, the Falls Handicap Inventory (FHI) 24 was used to assess handicaps associated with repeated falls. The participants received recommendations with regard to behavioral change, functional needs, and safety within the home environment.…”
Section: Interventionmentioning
confidence: 99%
“…21,22 Environmental hazards were identified and registered using a home-safety checklist. 23 In addition, the Falls Handicap Inventory (FHI) 24 was used to assess handicaps associated with repeated falls. The participants received recommendations with regard to behavioral change, functional needs, and safety within the home environment.…”
Section: Interventionmentioning
confidence: 99%
“…Selection of communitydwelling elderly with a high risk of falling is difficult. Several studies on the prediction of falls and recurrent falls in elderly people have been published [13,19], al-though mostly without evidence of feasibility. The aim of the present study, using data from a large prospective cohort of elderly, including similar numbers of men and women, is to develop a fall-risk screening test for community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Only two authors reported sensitivity and specificity of checklists items [ 62 , 103 ]. Thirty studies reported inter-rater reliability [ 8 , 14 , 15 , 19 , 23 , 51 , 54 , 57 59 , 72 , 77 , 80 , 81 , 84 , 85 , 98 , 103 , 106 , 110 112 , 115 , 120 123 , 133 , 135 , 152 ]; fewer reported test-retest reliability [ 36 , 81 , 98 , 122 ] or internal consistency [ 53 , 81 , 86 , 97 ]. The inter-rater reliability of checklists, when used by professional and lay older adult pairs, was reported in four studies; three showed that professionals identified more hazards than lay older adults [ 23 , 111 , 133 ] and one showed that lay older adults reported more of some hazards, while professionals reported more of other hazards [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…From these documents, 42 unique checklists were identified and included in the second stage of this review [ 8 , 15 17 , 20 23 , 34 , 44 , 49 , 51 , 53 , 58 , 66 , 69 , 72 , 79 , 82 , 86 , 87 , 98 , 102 , 108 , 110 112 , 115 , 121 , 124 , 126 , 132 , 135 , 137 , 139 , 140 , 144 , 148 – 152 ].…”
Section: Methodsmentioning
confidence: 99%